Two new species of Pinguicula (Lentibulariaceae) from central and northern Mexico - Zamudio, Sergio (Instituto de Ecología, A.C., 1988)
Two new species of Pinguicula are described from Mexico: P. crassifolia (subg. Pinguicula) from Las Ventanas, municipality of El Chico, Hidalgo, and P. gracilis (subg. Temnoceras) from Cerro de las Mitras, municipality of Monterrey, Nuevo León.